Study the Effects of the IL-1β -511 C>T Rs16944 SNP on the Incidence of Cardiomyopathy - Saeed Al-Mafragy, Hussein; Hamzah, Elham F.; Neema AL-Mussawy, Ahmed; H. Kzar, Hamzah; A. Al-Rubaie, Zahraa (Clinical Medicine And Health Research Journal, 2023)
Background: The diseases that involve the myocardium directly and are not the result of hypertension, congenital, vascular, coronary, or pericardial abnormalities are called cardiomyopathy (CM). It is known that interleukin-1 (IL-1) family cytokines involve in inflammation and immune regulation and act as an important role in innate and adaptive immunity. Aim: In this study, it was investigated the antioxidant capacity and their relation trace elements in cardiomyopathy CM patients and its correlation with IL-1β -511 C>T rs16944 SNP. Methods: TAOC, and Cu-Zn SOD were determined by ELISA, and Cu and Zn were assessed by spectrophotometric method. IL-1β -511 C>T rs16944 SNP was assessed by PCR and DNA sequencing. Results: The results were conducted that no statistically significant difference in age between CM and CONT groups (P>0.05). The results showed that was a statistically significant decrease in TAOC and SOD levels in the CM group compared to the CONT group (P<0.001). There was a statistically significant decrease in Cu and Zn levels in the CM group compared to the CONT group (P<0.001). Conclusion: This study suggested that the essential role of antioxidant capacity and their trace elements affected by IL-1β -511 C>T rs16944 SNP as a risk factor for the incidence of CM in the Iraqi population.